Negotiating Women's Veiling : Politics & Sexuality in Contemporary Indonesia - Dewi Candraningrum (Institut de recherche sur l'Asie du Sud-Est contemporaine, 2013)
This study will focus on the Indonesian jilbab, an ubiquitous piece of cloth that covers the hair and neck of women tightly, leaving no skin unconcealed. Achievement and role of jilbab after the authoritarian regime of Soeharto in 1998 is hardly known. The author examines women perception but also the Sharia Ordinances and the narratives of censorship. Voices of both women and sexual minorities (transgenders, gays, lesbians, bisexuals and queers) finally demonstrate awareness of the politics of representation in contemporary Indonesia, highlighting the links between religion, politics and identity.